G332(P) Epidemiology of adolescent trauma in england: a review of tarn data 2008–2017, in collaboration with peruki. (May 2019) - Roberts, Z; Collins, JA; James, DR; Lyttle, MD; Roland, D; Mullen, S
Abstract : Background: Trauma contributes significantly to adolescent morbidity and mortality. There is currently a dearth of literature specific to this field in the UK. We aimed to ascertain the epidemiology of adolescent trauma in England. Methods: TARN (Trauma Audit Research Network) records all trauma cases which meet pre-specified criteria. Adolescents were defined as 10–24 years. TARN data from English sites over a ten-year period (2008–2017) were included in this analysis. Results: TARN recorded 26 330 cases of adolescent trauma with 5266 (20%) aged 10–15 years and 21 064 (80%) aged 16–24 years. The median age was 19.4 years (IQR 16.7–21.7 years). There was a 2.2-fold increase in the annual number of cases reported during the period of study with an increase in the number treated in MTCs (44% 2008 vs 73% 2017). A male predominance was noted (76.7%). Trauma was more likely to occur between 08.00 and 00:00 (77.4%), at weekends and between April and October. Mortality rate was 4.4% (4.47% in 16–24 year old group and 3.84% in 10–15 year old group). Road traffic collision (RTC) was the leading cause of adolescent trauma (52%). Intentional injuries accounted for 19.8%; 16.2% alleged assault and 3.6% suspected self-harm. There was a potential three-fold increase in the number of stabbings reported, resulting in an increase in the proportion of trauma due to stabbings over the study period (9.3% in 2008 to 12.2% in 2017). Those with a known psychiatric diagnosis had a higher mortality (6.5% vs 4.2%; p<0.001). Conclusions: There has been an increase in reported adolescent trauma with RTC and intentional injuries, including stabbings as leading aetiologies. Health care professionals and policy makers need to prioritise national preventative public health measures and early interventions to reduce the incidence of trauma in this vulnerable age group.